Unraveling Barriers to Addressing Domestic Violence Cases at the Cilacap Police Department - Shellyana Putri; Nourma Dewi; Yulian Dwi Nurwanti (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Domestic violence (DV) constitutes a violation of human rights that remains widespread and is frequently regarded as a private matter, thereby hindering victims from obtaining adequate legal protection. This study aims to examine the role of investigators within the Women and Children’s Service Unit (PPA) of the Cilacap Police Department in addressing domestic violence cases, as well as to identify the challenges encountered in the process. The research employs an empirical legal method with a socio-legal approach, utilizing interviews, observations, and document analysis, all of which are examined qualitatively. The findings reveal that PPA investigators are actively involved in receiving reports, providing victim protection, conducting investigations, collecting evidence, and coordinating with relevant agencies. However, several key challenges persist, including limited resources, difficulties in evidentiary proof, withdrawal of complaints, familial pressure, economic dependency, and prevailing socio-cultural norms. In conclusion, effective handling of domestic violence cases necessitates institutional strengthening, enhanced victim protection mechanisms, and transformation of the community’s legal culture.